Les concepts nomades. Voyage du concept de médiation de la didactique des langues aux sciences infirmières - Demont, Guillaume (Neofilolog, 2023)
Globalization has increased contacts between researchers of different nationalities (more and more international conferences, European research programmes, online access to scientific publications, etc.). This increase in contacts has led to a mobility of concepts. Language teaching is no exception to this trend. By tackling subjects that are also dealt with by other disciplines, it is enriched by nomadic concepts that it appropriates and adapts to its own disciplinaryrepertoire. This can be illustrated by considering one such concept in the teaching of French as a professional language (FLP) where the teacher applies a concept taken from language teaching, which is also used in the professional sector that is being studied. In this article, we will study how the concept of mediation is both structuring for language didactics and for the nursing sciences. We will then look at how the teachercan use this concept of ‘mediation’ as a lever to apply the results of their analysis of the profession in a training system that corresponds to the professional habitus of the target audience. To do this, we will use the development of a course for foreign nurses working in France in psychiatry.